1980
DOI: 10.1126/science.6996094
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Activity in Photocopies

Abstract: Extracts from several different photocopies were mutagenic in the Ames Salmonella assay. The mutagenic behavior was similar for extracts from copies and corresponding toners indicating that toners are directly responsible for the mutagenicity. The mutagenicity is caused by at least two classes of compounds which may be present either alone or in combination in any toner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…The operators are exposed to toner (while reloading and unloading the machines) and to toxic gases like ozone, nitrogen dioxide, volatile organic compounds and extremely low frequency electromagnetic fields during their operation [8][9][10][11][12] . Majority of these agents have been reported to be mutagenic or genotoxic in either bacterial or mammalian systems.…”
Section: Introductionmentioning
confidence: 99%
“…The operators are exposed to toner (while reloading and unloading the machines) and to toxic gases like ozone, nitrogen dioxide, volatile organic compounds and extremely low frequency electromagnetic fields during their operation [8][9][10][11][12] . Majority of these agents have been reported to be mutagenic or genotoxic in either bacterial or mammalian systems.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] So far, there is only one published report where authors Goud et al, [5] indicated that individuals working with photocopying machines have an increased basal DNA damage, as measured by comet assay.…”
Section: Introductionmentioning
confidence: 99%
“…(18)(19)(20) and are a class of chemicals that present a risk as genotoxic pollutants. First detected in the environment as components of carbon black phototoners (21), nitrated PAHs may be formed as a result of nitration with 03, NO2, and peroxyacetyl nitrate in airborne pollutants (22,23) or as a result of a variety of combustion processes (24)(25)(26), including the incomplete burning of diesel fuel (27)(28)(29)(30)(31)(32)(33)(34)(35). They are not only ubiquitous in the atmosphere but may also be present in high concentrations in confined spaces (e.g., office and home environment) primarily as a result of cigarette smoking (34,36,37).…”
Section: Nitropolynuclear Aromatic Hydrocarbonsmentioning
confidence: 99%